Synergistic Effects of Chlorination and Branched Alkyl Side Chain on the Photovoltaic Properties of Simple Non‐Fullerene Acceptors with Quinoxaline as the Core. Issue 17 (1st June 2021) - Ye, Shounuan; Chen, Shuaishuai; Li, Shuixing; Pan, Youwen; Xia, Xinxin; Fu, Weifei; Zuo, Lijian; Lu, Xinhui; Shi, Minmin; Chen, Hongzheng
Abstract: To date, the fused‐ring electron acceptors show the best photovoltaic performances, and the development of simple non‐fullerene acceptors via intramolecular noncovalent interactions can reduce synthetic costs. In this work, four simple non‐fullerene acceptors with an A‐D‐A'‐D‐A configuration (QCIC1, QCIC2, QCIC3, and QCIC4) were synthesized. They contained the same conjugated backbone (A': quinoxaline; D: cyclopentadithiophene; A: dicyano‐indanone) but different halogen atoms and alkyl side chains. Due to the chlorination on the end‐groups and the most and/or longest branched alkyl side chains on the backbone, the blended film composed of QCIC3 and donor poly{[2, 6′‐4, 8‐di(5‐ethylhexylthienyl)benzo [1, 2‐b : 4, 5‐b′]dithiophene]‐ alt ‐[5, 5‐(1′, 3′‐di‐2‐thienyl‐5′, 7′‐bis(2‐ethylhexyl)benzo[1′, 2′‐c : 4′, 5′‐c′]dithiophene‐4, 8‐dione)]} (PBDB‐T) exhibited the strongest π‐π stacking and the most suitable phase‐separation domains among the four blended films. Therefore, the QCIC3‐based organic solar cells yielded the highest power conversion efficiency of 10.55 %. This work provides a pathway to optimize the molecular arrangements and enhance the photovoltaic property of simple electron acceptors through subtle chemical modifications. Abstract : Best of four : Four simple non‐fullerene acceptors (NFAs) are designed with the same conjugated backbone but varied halogen atoms and alkyl side chains. Through synergistic effects of chlorination and branched alkyl side chain, the QCIC3‐based organic solar cell shows the highest power conversion efficiency of 10.55 % due to more optimized π‐π stacking and morphology. This work provides a reference to better understand the structure‐property relationships of simple NFAs bearing an A‐D‐A'‐D‐A architecture.